A Comparison of Ambulatory Surgery Center Production Costs and Medicare Payments: Evidence on Colonoscopy and Endoscopy. Issue 2 (February 2016) - Mitchell, Jean M.; Carey, Kathleen
Abstract : Background: Ambulatory surgery centers (ASCs) are freestanding facilities that specialize in surgical and diagnostic procedures that do not require an overnight stay. While it is generally assumed that ASCs are less costly than hospital outpatient surgery departments, there is sparse empirical evidence regarding their relative production costs. Objectives: To estimate ASC production costs using financial and claims records for procedures performed by surgery centers that specialize in gastroenterology procedures (colonoscopy and endoscopy). Research Design: We estimate production costs in ASCs that specialize in gastroenterology procedures using financial cost and patient discharge data from Pennsylvania for the time period 2004–2013. We focus on the 2 primary procedures (colonoscopies and endoscopies) performed at each ASC. We use our estimates to predict average costs for each procedure and then compare predicted costs to Medicare ACS payments for these procedures. Results: Comparisons of the costs of each procedure with 2013 national Medicare ASC payment rates suggest that Medicare payments exceed production costs for both colonoscopy and endoscopy. Conclusions: This study demonstrated that it is feasible to estimate production costs for procedures performed in freestanding surgery centers. The procedure-specific cost estimates can then be compared with ASC payment rates to ascertain if payments are aligned with costs. This approach can serve as an evaluation template for CMS and private insurers who are concerned that ASC facility payments for specific procedures may be excessive.